Developing a sexual and reproductive health educational intervention for adolescent Syrian refugee girls: Challenges and lessons learned - Fahme, Sasha Abdallah; Khater, Beatrice; Dagher, Myriam; DeJong, Jocelyn; Abdulrahim, Sawsan (Frontiers in Reproductive Health, 2022)
In Lebanon, a country with the highest per capita refugee population in the world, roughly one in four persons is forcibly displaced. Early marriage is highly prevalent among Syrian refugees in Lebanon and qualitative studies suggest an unmet need for sexual and reproductive health (SRH) information and services in this community. Adolescent Syrian refugee girls in Lebanon are a vulnerable population at risk of negative SRH outcomes related to early sexual debut, which occurs primarily in the context of early marriage. Despite this need, cultural norms and gender roles generally restrict adolescent girls' access to SRH resources. To address this need for comprehensive sexuality education, our team developed a novel, rights-based, peer-led, adolescent SRH educational curriculum that is specific to the context of Syrian displacement in Lebanon. This curriculum was developed to be administered as part of Project Amenah, a community-based, multi-component intervention that aims to reduce early marriage and improve SRH among adolescent Syrian refugee girls displaced in Lebanon. The curriculum, which features eight discreet age-appropriate units, is based on extensive formative work conducted in this community, as well as adaptations of early marriage programs implemented in low-resource settings elsewhere. Topics covered include, but are not limited to, gender and human rights, communication, negotiation and decision-making, reproductive anatomy, puberty and menstruation, sexually transmitted infections, family planning and modern contraception, and adolescent pregnancy. We encountered several challenges when developing this curriculum, including those related to community acceptability, varying levels of literacy levels among participants, and limited engagement with married adolescents, who may experience mobility restrictions that preclude their participation. We recommend that investigators developing adolescent SRH interventions in similar settings utilize a behavior-determinant-intervention logic model to guide their study design, elucidate community priorities and capacity by conducting preliminary qualitative work and assembling a community advisory board, and follow a peer-led model, which has shown to be effective for adolescent SRH interventions.